Neuerwerbungen : 1985-1986. - Wilhelm-Lehmbruck-Museum, Duisburg (Duisburg : Wilhelm-Lehmbruck-Museum, 1986)
Baroni, Claudio ; Becherer, Detlef ; Bernhard, Franz ; Bosslet, Eberhard ; Brauner, Victor ; Bury, Claus ; Calder, Alexander ; Caro, Anthony ; Christian, Abraham David ; Christo ; Delahaut, Jo ; De Meulemeester, Emmanuel ; Ehlers, Karl ; Freundlich, Otto ; Gargallo, Pablo ; Gebert, Hansik ; etc.
Neuerwerbungen 1985-1986, Wilhelm-Lehmbruck-Museum der Stadt Duisburg, 7. September bis 2. November 1986
boek